EVALUASI JUMLAH PENGGUNAAN TRUK ANGKUTAN DI SUATU PERUSAHAAN HUTAN DI RIAU (An evaluation of the number of logging trucks used by a forest company in Riau) - Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1990)
A  study   of  the  number   of  logging trucks  used  by  a forest  company   in. Riau  was carried out  in 1989.  To  evaluate the  number   pf  logging  trucks,   transport   times  and  load.  volumes  of  logging trucks  were collected  through  a work  time study.   The  objective   is to find  out  the  number  of  loggine trucks   which  meets  the  logging company's   production   target. The  investigation   comes  up  to  the  following   conclusion:1.Log  number  and  load volume  averages hauled  by Nissan  TZ  52  logging trucks  were 4 logs/trip  and  23.84  m3 /trip, respectively.   At  the  distance  of  21 km,  the  logging trucks  normally  took  190.65  minutes  (3.18 hours)  to transport logs from  the  forest  to  log yard.  Logging  trucks  could  transport  logs three  round  trips per  day.2. The  normal  average productivity    of  the  logging trucks  was 71.52  m3  per  day.3.The average productive   time  of  logging trucks  was 80%  while  the average non  productive   time  was 20%.4. The  number   of  logging  trucks  available  was 2 units  which  conformed   with  the  company's   production    target. For better  operations:  it is recommended   that  the company  has one additional  logging truck  to meet  its production  target in the  next  working  plan.